Novel Quorum Quenching YtnP Lactonase From Bacillus paralicheniformis Reduces Pseudomonas aeruginosa Virulence and Increases Antibiotic Efficacy in vivo - Djokic, Lidija; Stankovic, Nada; Galic, Ivana; Moric, Ivana; Radakovic, Natasa; Šegan, Sandra; Pavic, Aleksandar; Senerovic, Lidija (Frontiers in Microbiology, 2022)
Bacterial infections have become increasingly difficult to treat due to the occurrence of antibiotic resistant strains. A promising strategy to increase efficacy of therapy is to combine antibacterials with the agents that decrease pathogen virulence via modulation of the quorum sensing (QS). Lactonases inhibit acylated homoserine lactone (AHL) mediated QS in Gram-negative bacteria, including the leading nosocomial pathogen Pseudomonas aeruginosa. Here we describe characteristics of heterologously expressed YtnP lactonase from Bacillus paralicheniformis ZP1 (YtnP-ZP1) isolated from agricultural soil using culture enrichment method. Purified YtnP-ZP1 hydrolyzed different AHLs with preference to substrates with long acyl residues as evaluated in assays with biosensors and HPLC. The enzyme showed good thermostability and activity in wide temperature range. YtnP-ZP1 in 50 µg mL-1 concentration reduced the amount of P. aeruginosa-produced long chain AHLs by 85%, while it hydrolyzed 50% of short chain AHLs. Incubation of P. aeruginosa PAO1 with YtnP-ZP1 reduced its swarming motility and elastolytic activity, without bactericidal effect. YtnP-ZP1 caused inhibition of biofilm formation and disintegration of mature biofilms in P. aeruginosa PAO1 and multiresistant clinical strain BR5H that was visualized by crystal violet staining. The treatment with YtnP-ZP1 in concentrations higher than 25 µg mL-1 improved the survival of P. aeruginosa PAO1-infected zebrafish (Danio rerio), rescuing 80% of embryos, while in combination with tobramycin or gentamicin survival rate increased to 100%. The treatment of P. aeruginosa PAO1 biofilms on infected zebrafish tail wounds with 50 µg mL-1 YtnP-ZP1 and 2  MIC tobramycin led to infection clearing in 2 days. The extensive toxicity studies proved YtnP-ZP1 non-toxic to human cells and zebrafish. In conclusion, novel YtnP-ZP1 lactonase with its effective anti-virulence activity could be used to increase the efficacy of clinically approved antibiotics in clearing both systemic and biofilm-associated P. aeruginosa infections.